Metal Organic Frame-Upconverting Nanoparticle Assemblies for the FRET Based Sensor Detection of Bisphenol A in High-Salt Foods - Xu, Zhou; Zhang, Lin-wei; Long, Ling-li; Zhu, Shao-hua; Chen, Mao-long; Ding, Li; Cheng, Yun-hui (Frontiers in Bioengineering and Biotechnology, 2020)
To resolve the occurrence of unfulfillable detection in high-salts foods, we used fluorescence resonant energy transfer (FRET) sensors based on nanoparticle upconversion. In this study, we developed a novel FRET sensor for the detection of bisphenol A (BPA) in high-salt foods. We based this approach on the assembly of aptamer modified upconversion nanoparticles (DNA1-UCNPs) and complementary DNA modified metal organic frames (DNA2-MOFs), which possessed corresponding wavelength absorption. Targeting BPA signal transduction was performed using the BPA aptamer, via competitive recognition between the BPA analyte and complementary DNA sequences in a high-salt solution. Sensor adaption in high-salt samples was attributed to functional hydrophilic groups, modified in the MOFs, and the enhanced colloidal stability of these MOFs. The MOF-UCNP assembly displayed considerable analytical performance in terms of BPA detection, with a linear range of 0.1–100 nM, and a limit of detection (LOD) of 0.02 nM, in a 340 mM NaCl food sample (the energy drink, Gatorade). Thus, this method provides a solid basis for small molecules detection in high-salt foods.